Stem cell transplantation outcomes in lymphoblastic lymphoma. Issue 2 (1st February 2017) - Brammer, Jonathan E.; Khouri, Issa; Marin, David; Ledesma, Celina; Rondon, Gabriela; Ciurea, Stefan O.; Nieto, Yago; Champlin, Richard E.; Hosing, Chitra; Kebriaei, Partow
Abstract: Lymphoblastic lymphoma (LBL) is an aggressive lymphoma pathologically similar to lymphoblastic leukemia, but primarily presents with nodal or extra-medullary involvement. The aim of this study is to describe outcomes of patients undergoing stem cell transplantation (SCT) for LBL compared to historical data. Thirty-nine patients, of which 54% lacked complete remission (CR), received SCT for LBL between 1990 and 2015; 31 allogeneic and eight autologous. Overall survival (OS) and progression free survival (PFS) at three years for the entire cohort was 41%, the cumulative incidence (CI) of non-relapse mortality (NRM) was 18% at one year, and CI relapse mortality was 28% at one-year and 36% at three years; results similar to historical reports. On multivariate analysis, the use of total-body irradiation (TBI) based conditioning and transplantation in CR were independently predictive of OS and PFS. For patients requiring SCT for LBL, CR and TBI-based conditioning prior to allogeneic SCT may provide improved disease control.